Аналіз залишкової міцності корпусу відцентрового насосу великої потужності з урахуванням ефекту корозійного зношення його елементів під час тривалої експлуатації - Ларін, Олексій Олександрович; Потопальська, Ксенія Євгенівна; Четверікова, Анастасія Дмитрівна (Національний технічний університет "Харківський політехнічний інститут", 2019)
У даній статті була проведено дослідження для визначення залишкової міцності відцентрового насосу, що працює в понад проектний термін експлуатації в лінії насосів енергоблока АЕС. Оцінка статичної міцності проводилась для основного екс-плуатаційного режиму роботи насоса(при нормальних умовах експлуатації).Проведено розрахунки для отримання параметрів НДС з яких визначено вплив рівню стоншення стінки корпусу насоса на виникаючі еквівалентні напруження, з використанням розроблених розрахункових тривимірних СЕ-моделей, які враховують фактичну геометрію деталей насоса і прогноз її можливої зміни на період продовженого ресурсу. Відповідні дослідження проведено в рамках чисельного комп’ютерного моделювання на основі методу скінченних елементів з використанням сучасних програмних комплексів.

In this paper, a study was conducted todetermine the residual strength of a centrifugal pump operating beyond the design lifetime of the pump unit of a NPP unit. Static strength assessment had beenperformed for the main operating mode of the pump (under normal operating conditions). Calculations were made to obtain the deformated state parameters, which were depend on determined the effect of the thinning of the pump housing wall on the resulting equivalentstress, using the developed calculated three-dimensional CE models, which take into account the actual geometry of the pump parts and the forecast of its possible change for the extended life period. To study the deformated state at the pump in normal operating conditions had been taken into account the prestressed state from tightening the pump caps and the uneven temperature distribution across the housing wall and the covers, as well as the uneven distribution of internal pressure, that is, a linearly distributed pressure from the inlet pipe to the pressure head. With increasing corro-sion inside the housing, the stress is increased while on the paw it is decreased. The stresses are distributed evenly and monotonically across the points selected for analysis. The relevant studies have been conducted in the framework of numerical computer modeling based on the finite element method using modern software systems.
Analysis of the residual strength of the high-capacity centrifugal pump with taking into account the effect of corrosive wear due to long-term exploitation
Keywords: енергетичне обладнання; powerengineering equipment